ANALYSIS OF THE CURRICULUM, PROGRAM AND QUALIFICATION REQUIREMENTS FOR IMPROVING STUDENTS' ORAL SPEAKING SKILLS BASED ON MODERN METHODOLOGICAL REQUIREMENTS (Universal International Scientific Journal, 2026)
This thesis analyzes the curriculum, subject program, and qualification requirements for the development of students' oral skills in higher education based on modern methodological criteria. The study uses content analysis of documents and competency-based expertise to develop scientific conclusions on the compatibility between oral indicators, assessment criteria, and methodological support.
Keywords: oral speech; competence approach; curriculum